1987
DOI: 10.3109/00016348709083032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pelvic Outlet Capacity on Labor: A prospective pelvimetry study of 1429 unselected primiparas

Abstract: The influence of pelvic outlet capacity on labor and the efficiency of routine low-dose radiological pelvimetry to anticipate dystocia during labor were studied prospectively among 1,429 unselected term primiparas, all having fetal head presentation and normal pregnancy. Outlet contraction was found in 0.9% and borderline outlet measurement in 5.3%. In 1,402 cases labor started spontaneously and 83 emergency cesarean sections were done. The incidence of cesarean section because of dystocia increased in inverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The reason is likely due to changes in practice in Sweden, where pelvic radiographs have almost disappeared. The decline of these examinations followed reports on their poor reproducibility, and poor predictability for the course of labor with cephalic presentation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The reason is likely due to changes in practice in Sweden, where pelvic radiographs have almost disappeared. The decline of these examinations followed reports on their poor reproducibility, and poor predictability for the course of labor with cephalic presentation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Cephalopelvic disproportion occurs when the pelvis does not accommodate for the passage of the fetal head, increasing the incidence of interventional delivery and the risk to both mother and infant 1,2 ; it is responsible for 8% of maternal deaths worldwide 3 . Floberg et al 4 reported a 0.9% incidence of contracted outlet among 1429 unselected term nulliparae, of whom 85% were delivered by Cesarean section (CS). The incidence of CS increased in proportion to decreasing pelvic outlet capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Today the presence of inlet and outlet contracted pelvis is estimated to 0.15 and 0.9% respectively, although borderline outlet contracted pelvis is estimated to be about 5% [13]. Mean birth weight has been stable during the last decades.…”
Section: Discussionmentioning
confidence: 99%